Tax Accounting Implications of the 15% Global Minimum Tax Policy for Multinational Enterprises in Indonesia - Mega Arum; Ferry Citra Febrianto; Intan Rahma Sari (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Economic globalization and tax avoidance practices through Base Erosion and Profit Shifting (BEPS) have driven the OECD/G20 initiative to implement a 15% Global Minimum Tax (GMT) under Pillar Two. This study aims to analyze tax accounting challenges in the implementation of GMT among multinational enterprises in Indonesia and its implications for fiscal policy and tax compliance. The study employs a qualitative descriptive approach based on a literature review method, analyzing regulatory documents, academic literature, and official reports. The findings indicate that GMT implementation generates challenges in four main areas: reconciliation between financial and tax reporting systems, harmonization of domestic regulations with international standards, reduced effectiveness of fiscal incentives in attracting investment, and increased demands for digital-based tax administration and compliance. The study concludes that GMT has a dual impact, enhancing global tax fairness and potential state revenue while simultaneously increasing compliance complexity and reducing fiscal competitiveness. This study implies that Indonesia needs to strengthen regulatory capacity, accelerate tax digitalization, and develop performance-based incentive schemes to maintain investment attractiveness while ensuring compliance with global tax standards.